2021
DOI: 10.1002/adsc.202001535
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Three‐Component Cascade Reaction of Benzaldehyde with Benzylamine and Hydroxylamine or Aniline: Synthesis of 1,2,4‐Oxadiazoles and Quinazolines

Abstract: The analogous three‐component synthesis strategy for substituted 1,2,4‐oxadiazole and quinazoline derivatives from readily available benzaldehyde, benzylamine and hydroxylamine or aniline has been developed. Both the cascade reaction sequences involves nucleophilic addition of C−N bond, introduction a halogen donor, nucleophilic substitution and Cu(II)‐catalyzed aerobic oxidation. This synthesis methodology demonstrated good yields, broad substrate scope and oxygen as a green oxidant. Thus, this synthesis prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Recently, in 2021, Liu et al demonstrated a one-pot three component annulation approach for the synthesis of quinazoline derivatives through the reactions of diversely substituted benzaldehyde (18), benzyl amine (42) and anilines (12) (Scheme 27b) [80]. In addition, these authors described the electronic effect of various substituents on the benzene ring and observed that electron-donating substituents were well tolerated in comparison to substrates containing electron-withdrawing groups.…”
Section: Copper-catalyzed Protocolsmentioning
confidence: 99%
“…Recently, in 2021, Liu et al demonstrated a one-pot three component annulation approach for the synthesis of quinazoline derivatives through the reactions of diversely substituted benzaldehyde (18), benzyl amine (42) and anilines (12) (Scheme 27b) [80]. In addition, these authors described the electronic effect of various substituents on the benzene ring and observed that electron-donating substituents were well tolerated in comparison to substrates containing electron-withdrawing groups.…”
Section: Copper-catalyzed Protocolsmentioning
confidence: 99%
“…The cascade reaction proceeded with the treatment of benzaldehyde 9 , benzylamine 33 , and aniline 102 in the presence of CuBr 2 and 1,10-phenanthroline in dibromohydantoin (DBH) with triethylamine and toluene in O 2 at 100°C for 14 h to produce quinazolines 103 in 30%–85% yields ( Scheme 14C ). ( Wang et al, 2021 ) The broad substrate scope, ease of scale-up to 1.72 g with 68% yield, and oxygen as a green oxidant are the advantages of this protocol. This is the first analogous three-component synthesis that employs benzaldehyde, benzylamine, and aniline for the assembly of quinazoline derivatives.…”
Section: First-row Transition Metal Catalystsmentioning
confidence: 99%
“…The selective oxidation of benzyl alcohol to its valuable intermediates and key commercial raw materials such as benzaldehyde, benzoic acid, and benzyl benzoate (BBz) holds significant interest at both fundamental and industrial levels. , Benzaldehyde and benzoic acid are used as precursors for different organic transformation reactions including the amination process, the synthesis of pagoclone and azinaclone, the synthesis of oxadiazole, isoquinolone and isocoumarin derivatives, hydrobenzoin, and the production of imine . Benzyl benzoate is a major raw material commercially used in fine chemical engineering …”
Section: Introductionmentioning
confidence: 99%